Penguatan Kapasitas dan Kompetensi Panitia Pengawas Tempat Pemungutan Suara (PTPS) Kecamatan Ranteangin dan Kecamatan Wawo Kabupaten kolaka Utara - Adhe Ismail Ananda; Sulkifli. Ar; Mirnawati Mirnawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This activity aims to increase the capacity and competence of the Polling Station Supervisory Committee (PTPS) in Ranteangin District, North Kolaka Regency. PTPS plays an important role in ensuring the implementation of honest, fair, and transparent elections. However, limited understanding of election regulations and procedures is a challenge in carrying out supervisory duties. The method used in this program is debriefing, which includes providing structured material regarding election regulations, supervision techniques, handling violations, and reporting procedures. The debriefing was attended by 10 participants from all villages/sub-districts in Ranteangin District. The results of the evaluation showed a significant increase in the participants' understanding and skills related to their duties and responsibilities as PTPS. This program is expected to strengthen the role of PTPS in maintaining the integrity of the electoral process and supporting the realization of quality democracy at the local level